Irish coffee murder - Meier, Leslie; Hollis, Lee; Ross, Barbara, 1953- (Meier, Leslie. Lucy Stone mystery, 2023)
"Irish Coffee Murder" (Leslie Meier): Part-time reporter Lucy Stone is writing a piece for the Courier about four Irish step dancing students from Tinker's Cove on the cusp of making it big. But the story becomes headline news for all the wrong reasons when one girl's mother is found dead in her bathtub. Did a stage mom take rivalry too far, or is some other motive at play?